Religion is not about God : how spiritual traditions nurture our biological nature and what to expect when they fail - Rue, Loyal D. (New Brunswick, NJ : Rutgers University Press, 2005)
Annotation Thousands of religious traditions have appeared over the course of human history but only a relative few have survived. Since some speak of a myriad of gods, others speak of only one, and some recognize no gods at all, we can conclude that belief in a supernatural being is not the only thing that holds a faith tradition together. Volumes have been written attempting to prove the existence or non-existence of supernatural being(s). So, if religion is not about God, then what on earth is it about? In this provocative book, Loyal Rue contends that religion, very basically, is about us. Successful religions are narrative (myth) traditions that influence human nature so that we might think, feel, and act in ways that are good for us, both individually and collectively. Through the use of images, symbols, and rituals, religion promotes reproductive fitness and survival through the facilitation of harmonious social relations. Rue builds his argument by first assembling a theory of human nature, drawn from recent developments in cognitive science and evolutionary theory. He shows how cognitive and emotional systems work together and how they are conditioned by cultural influences, including religion. He then surveys the major religious traditions-Judaism, Christianity, Islam, Hinduism, and Buddhism-to show how each one, in its own way, has guided human behavior to advance the twin goals of personal fulfillment and social coherence. As all religions are increasingly faced with a crisis of intellectual plausibility and moral relevance, they are being rendered incapable of shaping behavior in ways that might prevent unsustainable patterns of human population and consumption. Rue warns that when religions outlive their adaptive utility, they become positive threats to human survival. Despite its bold and ambitious goals, this book is hostile to neither the idea of God nor religious life. Written respectfully throughout, Religion Is Not about God will appeal to a broad audience interested in issues of faith and science.
Annotation In the course of human history, thousands of religious traditions have appeared, each with distinctive patterns of meaning. Some speak of a myriad of gods, others speak of only one, while some recognize no gods at all. Volumes have been written attempting to prove the existence or non-existence of supernatural being(s). But, if religion is not about God, then what on earth is it about? In this provocative book, Loyal Rue contends that religion, very basically, is about us. More specifically, it is a series of strategies that aims to influence human nature so that we might think, feel, and act in ways that are good for us, both individually and collectively. Employing images, symbols, and rituals, religion's main goals are to promote reproductive fitness and survival through the facilitation of harmonious social relations. Rue builds his argument by first assembling a theory of human nature, drawn from recent developments in cognitive science and evolutionary theory. He shows how cognitive and emotional systems work together and how they are conditioned by cultural influences, including religion. He then surveys the major religious traditions--Judaism, Christianity, Islam, Hinduism, and Buddhism--to show how each, in its own way, has guided human behavior to advance the twin goals of personal fulfillment and social coherence. Rue also considers the prospects for religious traditions in the light of contemporary challenges. As all religions are increasingly faced with a dual crisis of intellectual plausibility and moral relevance, they are being rendered less capable of shaping behavior in ways that are usefully adaptive. Rue warns that when religions outlive their adaptive utility, theybecome positive threats to human survival. Despite its bold and ambitious goals, this book is hostile to neither the idea of God nor religious life in general. Rue acknowledges that both can coexist with the idea of religion.
Annotation If religion is not about God, then what on earth is it about? Loyal Rue contends that religion is a series of strategies that aims to influence human nature so that we might think, feel, and act in ways that are good for us, both individually and collectively.
Preface -- Introduction: Religon Generalized and Naturalized -- Part I. On Human Nature -- The Epic of Evolution -- The Evolution of Behavior -- The Education of Emotion -- The Nature of Religion -- Part II. On Spiritual Traditions -- Judaism -- Christianity -- Islam -- Hinduism -- Buddhism -- Part III. On the Future of Religion -- The Crisis of Influence -- Doomsday and Beyond -- Notes -- Index -- About the Author.
Includes bibliographical references (pages 369-380) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Psychology, Religious; Genetic psychology; Psychologie religieuse; Psychologie génétique.; psychology of religion; RELIGION -- Psychology of Religion; Genetic psychology; Psychology, Religious; Religionspsychologie; Philosophie; Religion; Genetische psychologie; Godsdienstpsychologie